Solid immersion facilitates fluorescence microscopy with nanometer resolution and sub-Ångström emitter localization - Wildanger, Dominik; Hell, Stefan (Advanced materials, 2012)
Exploring the maximum spatial resolution achievable in far-field optical imaging, we show that applying solid immersion lenses (SIL) in stimulated emission depletion (STED) microscopy addresses single spins with a resolution down to 2.4 ± 0.3 nm and with a localization precision of 0.09 nm.
Gesehen am 05.11.2018